PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN KEWARGANEGRAAN (PKn) MENGGUNAKAN PENDEKATAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) DI KELAS IV - SEPTIVIA, YENTI (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
Abstract This research was done based on the fact that the civics learning at schools was still teacher centered so that the students were not actively involved in the learning process. As a result, their learning outcomes were low. This research aimed at describing the improvement of students’ civics learning outcomes by using the TGT type of the cooperative learning approach at the fourth grade of SDN 01 Singkarak. The design of the research was class action research using both qualitative and quantitative approaches. The total score of the students’ learning outcomes increased from 72,19% in cycle I to 83,94% in cycle II. Thus, the TGT type of the cooperative learning approach successfully improved the students’ civics learning outcomes at SDN 01 SingkarakKata Kunci : Hasil belajar, pembelajaran PKn, pendekatan kooperatif tipe TGT